Proxies Affecting Environmental Degradation: A Comparative Analysis Between Developed and Emerging Countries - Saputra, Alvin Cahya (TRANSEKONOMIKA: AKUNTANSI, BISNIS DAN KEUANGAN, 2025)
This study explores the proxies of Environmental Degradation (CO2 and N2O) in developed and emerging countries from 2001 to 2021 using panel data regression to accommodate variations over time and across entities. The result confirms the pollution hypothesis in emerging countries where foreign direct investment significantly increases N2O emissions, highlighting the necessity for stricter environmental regulations. It also reveals that GDP growth correlates with rising CO2 and N2O emissions in these regions, due to their early industrial stages, while in developed countries, GDP growth is decoupled from CO2 emissions, reflecting more sustainable practices. Trade openness in emerging economies further contributes to increased N2O emissions through deforestation and agricultural expansion. Contrarily, population growth shows a significant negative impact on emissions, suggesting increased efficiency and environmental awareness with higher population densities. These findings emphasize the importance of tailored environmental policies to effectively address the diverse impacts of economic activities on emissions.